Investigation of the Effect of Organizational DNA Characteristics of Schools on Bureaucratic Tendency by Structural Equation Modeling - Nacar, Davut; Demirtaş, Zülfü (Kahramanmaras Sutcu Imam University, 2021)
The purpose of this research is to examine the effects of school organizational DNA characteristics on bureaucratic tendency according to teacher perceptions. The research was carried out in the relational survey model, which is one of the quantitative research methods. The population of the research consists of 2598 teachers working in high schools in the central districts of Kahramanmaraş - Onikişubat and Dulkadiroğlu in the 2019 - 2020 academic year, while the sample consists of 537 teachers working in these districts. Organizational DNA Characteristics Scale of Schools and Bureaucratic Characteristics Scale of Schools were used to obtain data in the study. In the study, the data were analyzed using the structural equation model. The communicative, entrepreneurial and bureaucratic school has a significant effect on the bureaucratic tendency.

Bu araştırmanın amacı, öğretmen algılarına göre okulların örgütsel DNA özelliklerinin bürokratik eğilime etkilerini incelemektir. Araştırma nicel araştırma yöntemlerden ilişkisel tarama modelinde gerçekleştirilmiştir. Araştırmanın evrenini 2019-2020 eğitim öğretim yılı Kahramanmaraş ili - Onikişubat ve Dulkadiroğlu merkez ilçelerindeki liselerde görev yapmakta olan 2598 öğretmen oluştururken örneklemini bu ilçelerde görev yapmakta olan 537 öğretmen oluşturmaktadır. Araştırmada veri elde etmek için okulların örgütsel DNA Özellikleri Ölçeği ve Okulların Bürokratik Özellikleri Ölçeği kullanılmıştır. Araştırmada veriler yapısal eşitlik modeli kullanarak analiz edilmiştir. İletişime açık, girişimci ve bürokratik okulun bürokratik eğilim üzerinde anlamlı bir etkisi vardır.
Okulların Örgütsel DNA Özelliklerinin Bürokratik Eğilime Etkisinin Yapısal Eşitlik Modellemesi ile İncelenmesi
Keywords: Other Fields of Education; Alan Eğitimleri